2016
DOI: 10.2147/hiv.s93789
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis–HIV coinfection: current challenges

Abstract: Leishmaniasis – human immunodeficiency virus (HIV) coinfection can manifest itself as tegumentary or visceral leishmaniasis. Almost 35 countries have reported autochthonous coinfections. Visceral leishmaniasis is more frequently described. However, usual and unusual manifestations of tegumentary leishmaniasis have been reported mainly in the Americas, but the real prevalence of Leishmania infection in HIV-infected patients is not clear. Regarding the clinical manifestations, there are some reports showing unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 82 publications
(110 reference statements)
0
41
0
4
Order By: Relevance
“…Selected studies reported the outcomes of patients treated with either SSG or MA according to the recommended WHO dosing regimen (20 mg/kg/day parenterally for 28-30 days) and contained data for 10 or more patients about the initial (end-of-treatment) and/or final (six-month follow-up) cure that permitted calculation of the proportion of treatment failures. Given that the efficacy of Sb(V) against VL in patients co-infected with HIV-1 has been shown to be reduced 17 , 18 , only studies in which fewer than 5% of patients were HIV-1 positive or all HIV-1 patients could be statistically excluded were selected. Study populations for which HIV-1 prevalence was not reported were included.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Selected studies reported the outcomes of patients treated with either SSG or MA according to the recommended WHO dosing regimen (20 mg/kg/day parenterally for 28-30 days) and contained data for 10 or more patients about the initial (end-of-treatment) and/or final (six-month follow-up) cure that permitted calculation of the proportion of treatment failures. Given that the efficacy of Sb(V) against VL in patients co-infected with HIV-1 has been shown to be reduced 17 , 18 , only studies in which fewer than 5% of patients were HIV-1 positive or all HIV-1 patients could be statistically excluded were selected. Study populations for which HIV-1 prevalence was not reported were included.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Enzyme Linked Immunosorbent Assay (ELISA) is another serological test which is more useful in detecting visceral leishmaniasis. Immunochromatographic tests such as rK39 test which is based on recombinant K39 antigen are also performed in the detection of leishmaniasis [13, 23]. In the diagnosis of CL, Leishmanin Skin Test (LST) can be used in order to measure delayed hypersensitivity caused by CL [24, 25].…”
Section: Diagnosis Of the Diseasementioning
confidence: 99%
“…66.7% (10 men/2 women) belong to the age [6,8,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Gender and Agementioning
confidence: 99%
“…Globally, 36.9 million people living with HIV with 2.0 million new infections per year [31]. 35 countries currently report cases of co infection (Leishmania/HIV) in in 2-12% of all cases of VL, This proportion increases dramatically [16].…”
Section: Diagnosis Of Leishmaniasis In Hiv-infected Patientmentioning
confidence: 99%